ECO-BEHAVIOR MEDIATING ROLE IN GREEN HUMAN RESOURCE MANAGEMENT ON ENVIRONMENTAL PERFORMANCE - Wahyu Shiddiqotul Muflihah; Fajar Kurniawan; Made Galih Wisnu Wardana; Yuni Siswanti (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This research aims to examine the role of eco-behavior in moderating the link between environmental performance and green human resource management. Environmental concerns need to be integrated into every business function to strengthen sustainability efforts. Various internal factors can contribute to improving an organization’s environmental performance.Methods: This study recruited 97 participants from the academic community at a university in Yogyakarta, Indonesia. The data were collected through questionnaires and analyzed using SmartPLS. The analysis included checks for validity and reliability, as well as hypothesis testing for both partial and mediation effects.Results: Research findings show that green human resource management contributes to better environmental performance. Eco-behavior also increases due to green HRM practices. In addition, eco-behavior enhances environmental performance. The relationship between green HRM and environmental performance is strengthened through the mediating role of eco-behavior.Conclusion and suggestion: The findings imply that effectively implementing green HRM policies can strengthen eco-friendly behavior within an organization. Such environmentally conscious actions from employees will ultimately enhance the organization’s environmental performance. Future studies could broaden this research by involving more respondents or exploring additional variables and settings. Research conducted across universities in Indonesia could integrate variables like green attitudes, green innovation, and green culture. Keywords: Eco-Behavior, Environmental Performance, Green Human Resource, Management